ANALISIS LAMA PERENDAMAN TERHADAP ORGANOLEPTIK DAN NILAI GIZI TEPUNG Wikau maombo (Manihot esculenta Crantz) - Marzwan, Marzwan (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2016)
Immersion is an alternative to improve the quality of wikau maombo flour. Immersion is a method used by the wider community in dealing with the security processing of bitter cassava to make wikau maombo flour to be safe for consumption. Besides immersion, preferences and nutritional value analysis of wikau maombo flour is also very important to investigate, then immersion, organoleptic and proximate analysis as a method for determining the quality of wikau maombo flour. This study aimed to determine the method of immersion of wikau maombo flour preferred by the panelists and determine the nutritional value (moisture, ash, fat, crude fiber content, protein content and starch content) The results of the study show favorite color panelists to 3.638% ( preferred), aroma 3.531% (preferred), flavor 3.653% (preferred) and texture 3.683% (preferred) and nutritional values: water content of 6.70% and 6.23%, ash content of 1.05% and 1.04% , fat content 0.50% and 0.34%, protein content 1.10% and 1.24%, the starch content 23.18% and 22.57% and 2.57% and 2.30% crude fiber. Keywords: Wikau maombo flour, immersion, organoleptic, nutritional value.